2016
DOI: 10.1007/s00402-016-2510-0
|View full text |Cite
|
Sign up to set email alerts
|

Injectable autologous chondrocyte transplantation for full thickness acetabular cartilage defects: early clinical results

Abstract: The injectable matrix associated ACT is a reliable procedure, yielding promising early results with a significant increase of all scores evaluated in patients with full thickness acetabular cartilage defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
1
18
2
1
Order By: Relevance
“…They monitored a significant improvement in the outcome scores at 16 months displayed in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score and NAHS [ 16 ]. Schroeder et al reported significant improvement in the iHOT33, mHHS and subjective hip value (SHV) scores in 20 patients with an average defect size of 5.05 cm 2 at 12 months follow-up [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They monitored a significant improvement in the outcome scores at 16 months displayed in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score and NAHS [ 16 ]. Schroeder et al reported significant improvement in the iHOT33, mHHS and subjective hip value (SHV) scores in 20 patients with an average defect size of 5.05 cm 2 at 12 months follow-up [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schroeder et al also excluded patients with radiographic signs of dysplasia. Patients with radiographic signs of osteoarthritis ≥ 1° according to Kellgren and Lawrence were also excluded [ 17 ]. Körsmeier et al in comparison does not specify exclusion criteria [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2 Fällen musste eine Rearthroskopie zur Lösung von Adhäsionen durchgeführt werden, wobei sich eine quantitativ und qualitativ gute Defektauffüllung zeigte. Aus einer weiteren Studie mit 20 konsekutiven Patienten bei vergleichbaren Indikationen und Knorpeldefekten (∅ Größe: 5,05 cm 2 , 2-6 cm 2 ) wurden ähnlich gute und statistisch signifikante Ergebnisse in den verwendeten Scores (mHHS, iHOT [international Hip Outcome Tool] und SHV [Sub-jective Hip Value]) 6-24 Monate nach injizierbarer ACT berichtet [70]. Es wurden keine altersabhängigen Ergebnisunterschiede gefunden.…”
Section: Bisherige Klinische Ergebnisse Nach Actunclassified